PENINGKATAN PRODUKSI DAN PENJUALAN PADA USAHA BOLEN PISANG “QIFA BAKERI” DI SEMEMI KIDUL-BENOWO-SURABAYA - Maulana, Alfin; Fitryani, Fitryani; Novantori, Hafizh; Herdiansyah, Nova (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
The business of making bread and moist cakes is a home-based endeavor that many people engage in within the Sememi Kidul-Benowo-Surabaya area. The high demand for bread and moist cakes presents a promising business opportunity. The tight competition requires the production of bread and moist cakes to actively engage in breakthroughs and innovations, so that their products remain appealing to consumers. The effort of producing bread and wet cakes as a small business also faces various challenges, including low turnover and production capacity, as well as weaknesses in marketing, particularly in the distribution channels for its products. This community service activity is carried out at a bakery and wet cake business called "Bolen Pisang" located in the Sememi Kidul-Sememi-Benowo area. The objectives of this activity are: 1) for the bakery and wet cake entrepreneurs to run their business professionally, creatively, and innovatively; 2) to expand the market for their products; and 3) to increase their production capacity. The activities in this service include improving the production time efficiency of Bolen Pisang, online marketing through social media, and implementing quality management to ensure that the production results of Bolen Pisang meet expectations, as well as providing equipment grants. Based on the implementation and evaluation of the results, it can be concluded that entrepreneurs producing bread and wet cakes can run their businesses professionally, creatively, and innovatively, there is an increase in production capacity due to rising customer demand, and an improvement in the quality of Bolen Pisang production results.